PROFITABILITY ANALYSIS OF PEPPER BREEDING BUSINESS CV. ENDATU MULYA IN GAMPONG BLANG PANYANG, MUARA ONE DISTRICT, LHOKSEUMAWE CITY - Latiful Rahmi; Riani Riani; Irada Sinta (Jurnal Mahasiswa Agribisnis, 2022)
The prospect of pepper commodities in Indonesia can be seen from the potential of the large domestic market. Indonesia is one of the largest pepper exporter countries. Pepper is one of the plants that breed with seeds, but many farmers prefer to stem cutting to develop it because it is more effective and afficient in the cultivation of pepper plants. Increasing of pepper with cuttings is more profitable because it produced a homogeneous plant population and has the same characteristics as the earlier seed, but it is difficult to abtain high quantities of quality plant material which causes the price of pepper seeds to be expensive because seedlings is still small scale, farmers do not pruning que to prefers to produce fruit and the age of plant material that is not appropriate. This study aims to determine how the level of profitability faced by Mr. Yusuf as the owner of the pepper nursery business. The research was conducted in Gampong Blang Panyang,, Muara Satu sub-district, Lhokseumawe City from Oktober  2018 until November 2018. Data analysis method used descriptive quantitative analysis to analize income, profit, break event point and profitability. The results showed the number of production in the last harvest  reached 102.000 pepper seeds. With total production cost of 201.060.580 IDR, in production process and total revenue of 714.000.000 IDR, in production process and profit of 512.939.420 IDR in production process. Pepper nursery farming business in Gampong Blang Panyang able to produce profitability level of 71,7%.